Factors Related To Adolescent Sex Behavior In Review Of The Health Belief Model - Abdul Sila; Rasniah Sarumi; Umar Wiranto; Saharudin (Politeknik Karya Persada Muna, 2022)
Baground: Research on factors that influence adolescent free sex behavior in terms of Health Belief Model in SMAN 1 Pasir Putih Muna Regency, has been carried out by observing several variables including the Presence of Vulnerability / Severity of Disease, Threat of Disease, Religiosity, Gender, and Social Media. The purpose of the study was to find out some of the factors that influence and cause adolescents to engage in free sex.Method: This research is a quantitative study, using the design of the Cross Sectional Study approach, with a population of 304 students, where the sample observed was 75 respondents, with sampling using the Simple Random Sampling technique, with a population of 304 students, where the sample observed was 75 respondents, with sampling using the Simple Random Sampling technique. Results: The results showed that there was a relationship between adolescent perception about the level of vulnerability / seriousness of disease due to free sex with adolescent free sex behavior, with a Chi Square value of 9,182 (p = 0.350),means having a lack of relationship. There is a relationship between adolescent perception about the level of threat of disease due to free sex with adolescent free sex behavior with a Chi Square value of 14.815 (p = 0.444), means having a moderate relationship. There is a relationship between religiosity and adolescent free sex behavior with a Chi Square value of 23,628 (p = 0.561) which means having a moderate relationship. There is a relationship between gender and adolescent free sex behavior with a Chi Square value of 16,000 (p = 0.462) means having a moderate relationship. There is a relationship between social media and adolescent free sex behavior with a Chi Square value of 25,000 (p = 0.577) which means having a moderate relationship. Conclusions: There is a relationship between social media and adolescent free sex behavior Keywords: Free Sexual Behavior, Vulnerability/Severity of Disease, Threat of Disease, Religiosity, Gender, Social Media